UV VIS STUDY IN INTERACTION ASTAXANTHIN AND GLYCATED BSA - Muhammad Irsyad Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2019)
Astaxanthin antioxidant activity has been reported to be more than 100 times greater than that of vitamin E against lipid peroxidation and approximately 550 times more potent than that of vitamin E for singlet oxygen quenching. The purpose of this study is to find out the best concentration of astaxanthin to reduce the uv absorbance from BSA glycated by using UV spectroscopy. Astaxanthin was dissolved in methanol at concentration (1 x 10-9– 1x10-10 mol/L) different concentrations, then added to BSA glycated 100mM and 500mM then observed with UV spectroscopy. From the UV spectroscopy observations at 284 nm wavelengths, the best results for astaxanthin concentration is 0.2x 10-9 and 1x10-10 mol/L , it shows the best concentration on its effect to reduce the absorbance on BSA conformation